2014
DOI: 10.1371/journal.pone.0106534
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Pathogenic Coronaviruses in Cats by Homologous Recombination between Feline and Canine Coronaviruses

Abstract: Type II feline coronavirus (FCoV) emerged via double recombination between type I FCoV and type II canine coronavirus (CCoV). In this study, two type I FCoVs, three type II FCoVs and ten type II CCoVs were genetically compared. The results showed that three Japanese type II FCoVs, M91-267, KUK-H/L and Tokyo/cat/130627, also emerged by homologous recombination between type I FCoV and type II CCoV and their parent viruses were genetically different from one another. In addition, the 3′-terminal recombination sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 58 publications
4
129
0
3
Order By: Relevance
“…There is consistent evidence from independent studies that serotype II viruses emerge via double homologous recombination between serotype I FCoV and CCoV Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). As a consequence of the recombination, approximately one-third (10 kb) of the serotype I FCoV genome including the S gene and the neighboring regions are replaced with the equivalent parts of the CCoV genome Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). Detailed sequence analyses of numerous serotype II FCoVs revealed that the 5 0 -recombination event occurs in the polymerase gene while the 3 0 -recombination site is located in the E or M genes.…”
Section: Fcov Serotypes and Cellular Receptor Usagementioning
confidence: 66%
See 1 more Smart Citation
“…There is consistent evidence from independent studies that serotype II viruses emerge via double homologous recombination between serotype I FCoV and CCoV Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). As a consequence of the recombination, approximately one-third (10 kb) of the serotype I FCoV genome including the S gene and the neighboring regions are replaced with the equivalent parts of the CCoV genome Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). Detailed sequence analyses of numerous serotype II FCoVs revealed that the 5 0 -recombination event occurs in the polymerase gene while the 3 0 -recombination site is located in the E or M genes.…”
Section: Fcov Serotypes and Cellular Receptor Usagementioning
confidence: 66%
“…Furthermore, serotype II FCoVs have predominantly been observed in Asia and they were reported to be responsible for up to 25% of the natural infections in those countries (Amer et al, 2012;An et al, 2011;Sharif et al, 2010). There is consistent evidence from independent studies that serotype II viruses emerge via double homologous recombination between serotype I FCoV and CCoV Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). As a consequence of the recombination, approximately one-third (10 kb) of the serotype I FCoV genome including the S gene and the neighboring regions are replaced with the equivalent parts of the CCoV genome Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014).…”
Section: Fcov Serotypes and Cellular Receptor Usagementioning
confidence: 99%
“…It was suggested that type II FCoV was arisen from a double recombination between type I FCoV and type II CCoV (Herrewegh et al, 1998;Terada et al, 2014). In FCoV-II 79-1146, the genomic region from ORF1b, ORF2 (encoding S protein), and ORF3c is derived from type II CCoV and the other regions are derived from type I FCoV (Herrewegh et al, 1998), suggesting that these genes are factors leading to differences in the virological properties between the FCoV serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…FCoV has been classified into types I and II according to the amino acid sequence of its S protein (Motokawa et al, 1995). Type II FCoV was previously suggested to be from recombination between type I FCoV and type II canine coronavirus (CCoV) (Herrewegh et al, 1998;Terada et al, 2014). Separate from these genotypes/serotypes, FCoV consists of two biotypes: low pathogenic feline enteric coronavirus (FECV: lowvirulent FCoV) and high pathogenic FIP virus (FIPV: virulent FCoV) (Pedersen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Serotype I viruses dominate in the field and account for up to 95% of FCoV infections (Hohdatsu et al, 1992;Addie et al, 2003), whereas the prevalence of type II FCoVs is much lower. Serotype II FCoVs emerged through homologous recombination between serotype I FCoVs and CCoVs (Herrewegh et al, 1998;Terada et al, 2014).…”
Section: Introductionmentioning
confidence: 99%